2005
DOI: 10.1261/rna.2900205
|View full text |Cite
|
Sign up to set email alerts
|

Rat1p and Rai1p function with the nuclear exosome in the processing and degradation of rRNA precursors

Abstract: Exoribonucleases function in the processing and degradation of a variety of RNAs in all organisms. These enzymes play a particularly important role in the maturation of rRNAs and in a quality-control pathway that degrades rRNA precursors upon inhibition of ribosome biogenesis. Strains with defects in 3 0 -5 0 exoribonucleolytic components of the RNA processing exosome accumulate polyadenylated precursor rRNAs that also arise in strains with ribosome biogenesis defects. These findings suggested that polyadenyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 30 publications
6
68
2
Order By: Relevance
“…As shown here and elsewhere (Fig. 2, 6, and 7) (16,43,48), rai1 mutations affect rRNA maturation at both ends of 5.8S rRNA. At the 5= end, Rai1 inactivation tips the scales in favor of the L form of 5.8S rRNA, in agreement with its function as a cofactor of Rat1.…”
Section: Discussionsupporting
confidence: 82%
“…As shown here and elsewhere (Fig. 2, 6, and 7) (16,43,48), rai1 mutations affect rRNA maturation at both ends of 5.8S rRNA. At the 5= end, Rai1 inactivation tips the scales in favor of the L form of 5.8S rRNA, in agreement with its function as a cofactor of Rat1.…”
Section: Discussionsupporting
confidence: 82%
“…However, Rrp6 has functions distinct from those of other exosome subunits, in 5.8S rRNA processing (Briggs et al, 1998;Allmang et al, 1999a,b). Most, if not all, studies related to nuclear mRNA surveillance in yeast have been shown to require Rrp6 but, importantly, core exosome subunits have neither been tested nor shown to contribute to this function (e.g., Hilleren et al, 2001;Libri et al, 2002;Zenklusen et al, 2002;Das et al, 2003;Thomsen et al, 2003;Hieronymus et al, 2004;Fang et al, 2005;Kuai et al, 2005;Roth et al, 2005;Davis and Ares, 2006;Vodala et al, 2008). Finally, and consistent with our findings here, recent data have shown that yeast Rrp6 has RNA processing functions independent of the core exosome (Callahan and Butler, 2008).…”
Section: Rrp6 Function Independent Of the Nuclear Exosomesupporting
confidence: 84%
“…Nonetheless, based on its initial purification in the yeast nuclear exosome, most if not all subsequent phenotypes associated with loss of Rrp6 have been equated with perturbation of the nuclear exosome. Remarkably, despite its numerous roles in ribonucleometabolic pathways (Briggs et al, 1998;Bousquet-Antonelli et al, 2000;Burkard and Butler, 2000;Hilleren et al, 2001;Jensen et al, 2001;Dichtl et al, 2002;Libri et al, 2002;Zenklusen et al, 2002;Das et al, 2003;Thomsen et al, 2003;Hieronymus et al, 2004;Fang et al, 2005;Kuai et al, 2005;Roth et al, 2005;Reis and Campbell, 2007), it is not essential for viability in yeast (Briggs et al, 1998). Thus, whether these nuclear functions are specific to Rrp6 and/or are occurring in the context of an exosome complex is unclear.…”
mentioning
confidence: 99%
“…Its exonuclease activity is similar to that of Xrn1p, but Rat1p/Xrn2p is present at only one-tenth of the abundance of Xrn1p (Poole and Stevens 1995). Rat1 mutants show defects in the 59 processing of 5.8s rRNA (Amberg et al 1992;Fang et al 2005) and of snoRNAs (Lee et al 2003), and in degradation of pre-mRNAs (Bousquet-Antonelli et al 2000). The N-terminal 765 amino acids of Rat1p correspond to residues 1-671 of Xrn1p; the most important difference within this region is the insertion of a bipartite nuclear localization signal in Rat1p.…”
Section: Introductionmentioning
confidence: 99%